Caribbean Food Cultures: Culinary Practices and Consumption in the Caribbean and Its Diasporas - Beushausen, Wiebke; Brüske, Anne; Uhl, Ana-Sofia; Helber, Patrick; Kloß, Sinah Theres (Postcolonial studies, 2014)
Biographical note: Wiebke Beushausen is a research assistant in the junior research group »From the Caribbean to North America and Back« and PhD candidate in literary studies at Heidelberg University. Anne Brüske (PhD) is the head of the junior research group »From the Caribbean to North America and Back« at Heidelberg University since October 2010. She holds a PhD in Romance literature from Heidelberg University (2008) and has taught in Basel, Lyon and Heidelberg. Ana-Sofia Commichau is a research assistant in the junior research group »From the Caribbean to North America and Back« and PhD candidate in literary studies at Heidelberg University. Patrick Helber is a research assistant in the junior research group »From the Caribbean to North America and Back« and PhD candidate in contemporary history at Heidelberg University. Sinah Kloß is a research assistant in the junior research group »From the Caribbean to North America and Back« and a PhD candidate in Social Anthropology at Heidelberg University.